2018
DOI: 10.1177/0363546518788064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Healing After Medial Meniscal Root Repair Using Second-Look Arthroscopy, Clinical, and Radiological Criteria

Abstract: Despite degenerative change progression, clinical outcomes were improved. The successful healing rate was 69.7% after repair of MMRTs. Compared with the unhealed group, the stable healed group showed better clinical outcomes and less degenerative change progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(95 citation statements)
references
References 29 publications
1
94
0
Order By: Relevance
“…As a result, various factors such as patient age, varus alignment, the severity of cartilage lesion, healing status of repaired MMRT, and the change in MME after surgery have been found to be relevant factors and have been applied in clinical practice. 10,11,31,34…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, various factors such as patient age, varus alignment, the severity of cartilage lesion, healing status of repaired MMRT, and the change in MME after surgery have been found to be relevant factors and have been applied in clinical practice. 10,11,31,34…”
Section: Discussionmentioning
confidence: 99%
“…These findings are not novel, as they are consistent with previous studies that showed overall degenerative changes in the knee joint over time despite clinical improvement after arthroscopic transtibial pull-out repair of MMRT. 9,11,31 Accordingly, although the prevention of osteoarthritis progression has been shown to be difficult, several studies have been performed to find factors influencing surgical outcomes to delay or minimize the degenerative change of the knee as well as to improve surgical outcomes as much as possible. As a result, various factors such as patient age, varus alignment, the severity of cartilage lesion, healing status of repaired MMRT, and the change in MME after surgery have been found to be relevant factors and have been applied in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al 15 evaluated the healing of the meniscal root injury using second-look arthroscopy. Seventy percent of patients were stably healed and presented higher scores (Hospital for Special Surgery and International Knee Documentation Committee scores) than those with unstable healing.…”
Section: Discussionmentioning
confidence: 99%
“…14 As an alternative to medial collateral ligament release, posterior portals increase accessibility to the posterior root area. 15 For the comparison between transtibial pullout repair and suture anchor repair, we compared the findings of the study by Chung et al 16 (transtibial pullout repair) with those of Feucht et al 8 (suture anchor). We concluded that currently, there is no consensus on the biomechanical superiority between the 2 techniques.…”
Section: See Related Article On Page 2189mentioning
confidence: 99%